A BIOGRAPHY OF G. ARGENT. (10th November 2020) - Wilkie, P.; Conlon, T.; Hardy, G.
Abstract : A biographic summary of the research of Dr Graham Charles George Argent (born 15 May 1941, died 24 April 2019) is presented, summarising his research career. Expedition information, including dates, collection number series and the names of collaborators, is given, as is a list of his publications, annotated with taxonomic decisions and the names of new species described within them.